Artificial intelligence for scientific research – large language models in manuscript preparation - Napieralski, Piotr; Wojciechowski, Adam; Korjonen-Kuusipuro, Kristiina (Human Technology, 2024)
Artificial intelligence has the potential to revolutionize scientific work. At the same time, the availability of large language models, coupled with high publication pressure, often distorts the way AI tools are used. This study highlights not only the potential of selected contemporary tools, but also the traps and risks that come with using AI tools in the preparation of scientific papers. Wise use of AI techniques can improve the efficiency of work, but an unprofessional approach results in journal clogging and devaluation of the traditional form of sharing scientific achievements.